Analysis of the Influence of Atom Peanut Product Marketing Strategy on Purchase Decision of Small and Medium Enterprises (SMEs) (Study at CV Ud Sanjaya in Natar, South Lampung) - saputra, agung syawal; M.Oktaviannur (PT Inovasi Pratama Internasional, 2025)
The purpose of this research is to examine how the 7P marketing mix strategy (product, price, promotion, place, people, process, and physical evidence) impacts consumer decisions to purchase peanuts at CV UD Sanjaya in Natar, South Lampung. This study uses a quantitative approach that combines descriptive and verificative techniques, along with purposive sampling for a sample of 100 respondents. Data were analyzed using multiple linear regression after questionnaires were collected from November to December 2024. With an R Square value of 0.855, this study's findings demonstrate that all seven Ps of the marketing mix significantly impact consumers' decisions to buy, indicating that the independent variables are responsible for 85.5% of the variation in purchasing decisions. Partially, all dimensions of the marketing mix show a significant influence with a significance value of < 0.05, where Physical Evidence has the strongest influence (β = 0.540). This study provides practical implications for the development of SME marketing strategies and suggests the importance of an integrated marketing approach that considers all the elements of the marketing mix to enhance consumer purchasing decisions